Undiagnosed Sjögren’s Syndrome Presenting as Mesenteric Panniculitis - Rebecca L. Burns; Sharukh J. Bhavnagri (Case Reports in Rheumatology)
Mesenteric panniculitis is a rare inflammatory and fibrotic process that affects the small intestine mesentery. It may occur following abdominal surgery or in association with a variety of conditions, including malignancy, infection, and certain autoimmune and inflammatory conditions. Herein, an unusual case of mesenteric panniculitis in a patient with primary Sjögren’s syndrome will be presented. The patient presented with abdominal pain, weight loss, sicca symptoms, fatigue, and arthralgia. An abdominal CT revealed mesenteric fat stranding and prominent lymph nodes of the small intestine mesentery. She was found on laboratory workup to have positive antinuclear and anti-SSa antibodies. Minor salivary gland lip biopsy revealed focal lymphocytic sialadenitis. The patient’s symptoms and CT findings improved with corticosteroids. This case suggests that Sjögren’s syndrome should be considered as an underlying disease process in the evaluation of patients with mesenteric panniculitis.